“Engines” of Growth, “Sponges” of Labor: A Study on Economic Transformation and the Kuznets Paradox in Kepulauan Riau - Farhan, Adhe Fadli; Setiawan, Azhari; Pratama, Ryan Anggria; Azizi, Okky Rizki; Asyikin, Azrul (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study investigates the relationship between structural transformation and regional inequality in Kepulauan Riau (Kepri), Indonesia, a province strategically located as an industrial and service hub yet marked by persistent disparities. While the Kuznets hypothesis suggests an inverted-U link between growth and inequality, evidence from archipelagic economies remains limited. The main purpose of this research is to assess whether Kepri follows or diverges from the Kuznets trajectory by analyzing sectoral shifts and their implications for inequality dynamics. Using provincial macro and microeconomic data, this study applies panel data econometrics and productivity decomposition techniques to evaluate both within-sector growth and labor reallocation effects. The results reveal that industrial expansion generates high productivity but limited employment opportunities, while services act as a labor sponge with weak welfare contributions. This dualistic pattern, termed the “structural change penalty,” has amplified inequality across sectors and regions rather than reducing it. The findings underscore the need for stronger industrial linkages, service sector upgrading, and inclusive regional policies to ensure that structural transformation fosters broad-based and equitable development. By shifting the analytical focus from the national to the sub-national level, this study contributes new insights into the role of local governance, spatial politics, and policy choices in shaping divergent development paths in Indonesia.